4(-3x+1)=-2(7x-5)

Simple and best practice solution for 4(-3x+1)=-2(7x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-3x+1)=-2(7x-5) equation:


Simplifying
4(-3x + 1) = -2(7x + -5)

Reorder the terms:
4(1 + -3x) = -2(7x + -5)
(1 * 4 + -3x * 4) = -2(7x + -5)
(4 + -12x) = -2(7x + -5)

Reorder the terms:
4 + -12x = -2(-5 + 7x)
4 + -12x = (-5 * -2 + 7x * -2)
4 + -12x = (10 + -14x)

Solving
4 + -12x = 10 + -14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14x' to each side of the equation.
4 + -12x + 14x = 10 + -14x + 14x

Combine like terms: -12x + 14x = 2x
4 + 2x = 10 + -14x + 14x

Combine like terms: -14x + 14x = 0
4 + 2x = 10 + 0
4 + 2x = 10

Add '-4' to each side of the equation.
4 + -4 + 2x = 10 + -4

Combine like terms: 4 + -4 = 0
0 + 2x = 10 + -4
2x = 10 + -4

Combine like terms: 10 + -4 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| 4y-2+y+23=7y+30-5y | | 23+n+6=34 | | 8/y+7=5/y | | (5/8)x-(3/2)=12 | | 9=-5v+7 | | 7.6x-2.3x=-95.4 | | 7+8x=2-5x | | (3/4)x-(1/2)=(1/4) | | -5+4n-7=8 | | 3(3x-4)+5x= | | (2/5)x-(1/5)=(3/5) | | -1/3x+2=4 | | 5/6d=3/15 | | 16x^2+8x-64=0 | | 8-12v-9v= | | 5x+12=7x+20 | | 2k-5/-5 | | 6x-(3x+8)=4x-43 | | 0.70x+0.05(4-x)=0.10(106) | | 5x^2+7x+20=7x^2+3-10 | | -327/180 | | 4x-44y=32 | | 4(4x^2+7x-1)= | | (4x+3)2=68 | | 4x+3(x-5)=2x+3 | | 5x/5=25 | | 30x+10=4x-5 | | 16x-7=5-14x | | 24=-5p-p | | 15+9+2x=x | | 6(7n-4)+7(4n-4)=18 | | 5m^2-160=-20m |

Equations solver categories